The Santa clause 3. The escape clause [videorecording (DVD)] / Santa Frost Productions Inc. ; Walt Disney Pictures ; Boxing Cat Films ; Outlaw Productions ; produced by Tim Allen, Robert F. Newmyer, Brian Reilly, Jeffrey Silver ; written by Ed Decter & John J. Strauss ; directed by Michael Lembeck. - Lembeck, Michael; Allen, Tim, 1953-; Short, Martin, 1950-; Mitchell, Elizabeth, 1970-; Lloyd, Eric (Walt Disney Home Entertainment : Distributed by Buena Vista Home Entertainment, 2007)
With another Christmas season fast approaching, Santa Claus/Scott Calvin is feeling even more pressure. Mrs. Claus is expecting a little Claus. She is also longing for the company of some "tall people." So Scott agrees to let her parents visit as long as they believe that they're really in Canada rather than at the North Pole. Further complicating matters is a visit by Scott's ex-wife, her husband, and their daughter, Lucy. A member of the Council of Legendary Figures, Jack Frost is a very bad boy. He is supremely jealous of the figures who have their own holidays, especially Santa. So he launches a plan to sabotage the toy factory and compel Scott to invoke the little-known Escape Clause and wish he'd never become Santa. The resulting evocation has Scott rewinding 12 years and juggles a full house of family and the mischievous Jack Frost, who is scheming to take over the 'big guy's' holiday.